The new sovereignty compliance with international regulatory agreements - Chayes, Abram 1922-2000; Chayes, Antonia Handler 1929- (Harvard Univ. Press, 1995)
The New Sovereignty argues that this approach is misconceived. Cases of coercive enforcement are rare, and sanctions are too costly and difficult to mobilize to be a reliable enforcement tool. As an alternative to this "enforcement" model, the authors propose a "managerial" model for ensuring treaty compliance. It relies on the elaboration and application of treaty norms in a continuing dialogue among the parties, international officials, and nongovernmental organizations - and it is this dialogue that generates pressure to resolve problems of noncompliance. In the process, the norms and practices of the regime themselves evolve and develop